Altered density, composition and microanatomical distribution of infiltrating immune cells in cutaneous squamous cell carcinoma of organ transplant recipients - Strobel, Sophia; Safferling, Kai; Lahrmann, Bernd; Hoffmann, Jochen; Enk, Alexander; Hadaschik, Eva; Grabe, Niels; Lonsdorf, Anke Susanne (British journal of dermatology, 2018)
Background The inflammatory tumour microenvironment is crucial for effective tumour control, and long-term immunosuppression has been identified as a major risk factor for skin carcinogenesis. In solid organ transplant recipients (OTRs) undergoing long-term pharmacological immunosuppression, an increased incidence of cutaneous squamous cell carcinoma (SCC) and more aggressive tumour growth compared with immunocompetent patients has been reported. Objectives To determine the density and phenotype of immune cells infiltrating SCC and surrounding skin in OTRs, and to characterize the microanatomical distribution patterns in comparison with immunocompetent patients. Methods We analysed immune cell infiltrates within SCC and at defined regions of interest (ROIs) of tumour-surrounding skin in formalin-fixed paraffin-embedded tissue of 20 renal transplant patients and 18 carefully matched immunocompetent patients by high-resolution semiautomated microscopy on complete tissue sections stained for CD4, CD8, CD20 and CD68. Results The overall immune cell density of SCC arising in OTRs was significantly reduced compared with immunocompetent patients. Particularly CD4+ infiltrates at the directly invasive margin and tumour vicinity, intratumoral CD8+ T-cell densities and the overall density of CD20+ tumour-infiltrating B cells were significantly reduced in the tissue of OTRs. Conclusions Immune cell infiltrates within SCC and at defined ROIs of tumour-surrounding skin in OTRs differ markedly in their composition and microanatomical distribution compared with tumours arising in immunocompetent patients. Our findings substantially broaden the understanding of how long-term systemic immunosuppression modulates the local inflammatory microenvironment in the skin and at the site of invasive SCC.